2019
DOI: 10.1186/s13104-019-4344-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of colistin, imipenem and ceftazidime against drug-resistant Pseudomonas aeruginosa and Acinetobacter baumannii isolates in the south of Iran

Abstract: Objective The present study aimed to determine in vitro activity of colistin and other agents against drug-resistant isolates of Pseudomonas aeruginosa and Acinetobacter baumannii . Results This in vitro study performed on a collection of non-fermenting Gram-negative bacilli (NFB) consist of 18 A. baumannii and 21 P. aeruginosa isolates. Non-duplicated isolates (one per patient) were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
2
6
1
4
Order By: Relevance
“…only in the range 19.2 -33.0% and for P. aeruginosa 55.6 -63.1% to ciprofloxacin, cefepime and piperacillintazobactam, but 83.4% to amikacin, indicating that for all tested antimicrobial agents other than colistin, at best only amikacin might serve as an empiric treatment option for P. aeruginosa infections. In contrast, overall susceptibility rates to colistin were 94.6 and 95.7% for P. aeruginosa and A. baumannii in isolates obtained from IAIs, UTIs and RTIs in the present study, which is in agreement with previously reported high susceptibility rates of both species in other countries (Ece et al, 2014;Malekzadegan et al, 2019). In addition, there was no visible trend of decreasing colistin susceptibilities toward 2017 in the different hospital departments and Chinese regions, except for a slight decrease in east Jiangzhe.…”
Section: Discussionsupporting
confidence: 93%
“…only in the range 19.2 -33.0% and for P. aeruginosa 55.6 -63.1% to ciprofloxacin, cefepime and piperacillintazobactam, but 83.4% to amikacin, indicating that for all tested antimicrobial agents other than colistin, at best only amikacin might serve as an empiric treatment option for P. aeruginosa infections. In contrast, overall susceptibility rates to colistin were 94.6 and 95.7% for P. aeruginosa and A. baumannii in isolates obtained from IAIs, UTIs and RTIs in the present study, which is in agreement with previously reported high susceptibility rates of both species in other countries (Ece et al, 2014;Malekzadegan et al, 2019). In addition, there was no visible trend of decreasing colistin susceptibilities toward 2017 in the different hospital departments and Chinese regions, except for a slight decrease in east Jiangzhe.…”
Section: Discussionsupporting
confidence: 93%
“…Polymyxins are usually drug of choice to treat infections caused by MDR Gram-negative bacteria [12]. Previously two comparable reports were available from southern region [10,29], but our study was the first report from our region in the north of Iran. Moreover, our results are consistent with reports from CANWARD study and SENTRY program suggests that colistin remains an available option for the treatment of infection caused by CRAB since the majority of isolates were susceptible to colistin [30,31].…”
Section: Discussionmentioning
confidence: 72%
“…Limited therapeutic options to treat infections caused by these drug-resistant strains request development of new drugs or recruiting the old ones [10]. Colistin (also known as polymyxin E) is a multicomponent polypeptide antibiotic and relatively old polymyxin that achieved its antimicrobial effect by acting directly on bacterial cell membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidrug-resistant Acinetobacter baumannii is an opportunistic pathogen that causes nosocomial infections [1][2][3]. Infections caused by this bacterium have a high prevalence in hospitalized and immunocompromised patients who are admitted to intensive care units [4,5]. These infections are ventilator-associated pneumonia, soft-tissue, urinary tract, and meningitis infections [6][7][8].…”
Section: Introductionmentioning
confidence: 99%